2019
DOI: 10.1016/j.pbiomolbio.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular impacts of photobiomodulation on bone regeneration: A systematic review

Abstract: Photobiomodulation (PBM) encompasses a light application aimed to increase healing process, tissue regeneration, and reducing inflammation and pain. PBM is specifically aimed to modify the expression of cellular molecules; however, PBM impacts on cellular and molecular pathways especially in bone regenerative medicine have been investigated in scattered different studies. The purpose of the current study is to systematically review evidence on molecular impact of PBM on bone regeneration. A comprehensive elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 96 publications
(204 reference statements)
0
20
0
6
Order By: Relevance
“…Many materials for controlled drug release have been developed with a focus on controlling the immune responses involved in damage repair and anti-infection activity [14,[18][19][20]. Photosensitive delivery systems can stimulate beneficial photochemical reactions or release active molecules, thereby affecting the metabolism of osteoblasts [21][22][23]. This strategy has broad prospects in bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Many materials for controlled drug release have been developed with a focus on controlling the immune responses involved in damage repair and anti-infection activity [14,[18][19][20]. Photosensitive delivery systems can stimulate beneficial photochemical reactions or release active molecules, thereby affecting the metabolism of osteoblasts [21][22][23]. This strategy has broad prospects in bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, further experiments are required in order to better understand the processes involved in osteogenic cell proliferation and differentiation induced by laser therapy on biomaterial surfaces. We suggest studies assessing the response of irradiated MC3T3‐E1 and, especially, stem cells, over a longer experimental interval, also analyzing osteoblastic differentiation, because the literature indicated that LLLI can up‐regulate numerous osteogenic factors, including Collagen type I, Runx‐2, osteopontin, and osteocalcin (Hosseinpour, Fekrazad, Arany, & Ye, 2019; Tani et al, 2018). In addition, experiments that explore the application of PLA associated with other polymers; those produced by electrospinning; submitted to surface functionalization techniques; and/or incorporating growth factors, for example, human morphogenetic protein (BMP), are also suggested (da Silva et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…After orthodontic force removal, a physiological repair would follow involving the deposition of uncalci ed-cementoid matrix, broblast-like cells and cementoblast cells as well as the detachment of clastic cells [63]. Past cellular [28] and molecular investigations [64] have documented LLLT's capacity to modulate the activities of osteoblasts and osteoclasts with bone-related biomarkers such as RANKL and OPG. This provides a biological explanation for adopting LLLT to prevent transitional relapse and OIIRR.…”
Section: Discussionmentioning
confidence: 99%